Leiomyoma of the broad ligament in an 8-year-old female Nigerian local pig (Sus scrofa): A Case Report - Michael Efeturi Okandeji; John Olusoji Abiola; Olawale Olawumi OLA; Monsuru Oladunjoye Tijani; Theophilus Aghogho Jarikre; Olanrewaju Samuel Olaifa; Abdulrauf Adekunle Usman; Moyinoluwa Julianah Onoja (Ovozoa: Journal of Animal Reproduction, 2026)
Leiomyomas are benign smooth muscle tumors most frequently arising from the uterus of intact female animals. Extra-uterine forms, including those originating from the broad ligament, are rare across species and hold diagnostic significance, particularly in older pigs. An 8-year-old, nulliparous Nigerian local pig with a history of repeated unsuccessful breeding and progressive abdominal enlargement was slaughtered for evaluation. Post-mortem examination revealed a large, firm, well-encapsulated intra-abdominal mass. The mass was carefully removed, weighed, and sampled for cytological and histological analyses. Representative tissue samples were fixed in 10% neutral buffered formalin, processed routinely, paraffin-embedded, sectioned at 5μm, and stained with Hematoxylin and Eosin. Grossly, the mass was solitary, spherical, and encapsulated, weighing approximately 8 kg, and measuring 28 × 20 ×15 cm. The cut surface was firm, white, whorled, with distinct lobulation. Cytology showed low cellularity with discrete spindled-shaped cells. Histologically, the tumor consisted of well-differentiated spindle cells arranged in interlacing fascicles, with elongated, blunt-ended nuclei and no detectable mitotic activity. Cellular atypia was minimal, and there was no evidence of necrosis, hemorrhage, or invasion. These features support a benign smooth muscle tumor consistent with leiomyoma. This case describes a rare extra-uterine leiomyoma of the broad ligament in a geriatric pig, contributing to limited reports in swine and highlighting its relevance in the differential diagnosis of intra-abdominal masses in aged female pigs.